Respuesta :
remove the parentheses
x^3-9x^2+27x-27-x^3+3x^2-3x+1+7x^2=21x-28
x^2+24x-26=21x-28
x^2+24x-26-21x+28=0
x^2+3x+2=0
factor the expression
(x+2)(x+1)=0
sooo x1=-2 x2=-1
x^3-9x^2+27x-27-x^3+3x^2-3x+1+7x^2=21x-28
x^2+24x-26=21x-28
x^2+24x-26-21x+28=0
x^2+3x+2=0
factor the expression
(x+2)(x+1)=0
sooo x1=-2 x2=-1
Answer:
(x - 3)³ - (x - 1)³ + 7x² = 7(3x - 4)
=> x³ - 9x² + 27x - 27 - (x³ - 3x² + 3x - 1) + 7x² - 21x + 28 = 0
<=> -2x² + 6x + 1 + 3x² - 3x + 1 = 0
<=> x² + 3x + 2 = 0
<=> (x + 1)(x + 2) = 0
<=> x + 1 = 0 or x + 2 = 0
<=> x = -1 or x = -2